IMPLEMENTATION OF LIVEABLE HOUSING PROGRAMS (RTLH) IN ALLEVIATING POVERTY IN BOLAANG UKI DIS-TRICT, BOLAANG MONGONDOW SELATAN REGENCY - Fice Nur; Titin Dunggio; Imam Mashudi (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This study aims to determine and analyze the implementation, and the supporting and inhibiting factors of the implementation of the Livable Housing Program (RTLH) in alleviating poverty in Bolaang Uki District, Bolaang Mongondow Selatan Regency. This study uses a descriptive method with a qualitative approach. The informants in this research were the Social Office, Head of Sub-District, Sangadi and community who received RTLH assistance. Data analysis through data reduction, display data and conclusion drawing/verification. The results showed the stages of implementation which included: Proposal verification, location assessment, socialization, location determination and verification of potential beneficiaries are deemed not maximally successful. The house construction stages include the assessment stage and the determination of the part of the house to be repaired and prioritization of the part of the house to be repaired is considered unsuccessful. Supporting factors are communication and disposition. While, inhibiting factors are the resources and structure of the bureaucracy.